A Study on Teacher Professionalism in Teaching English After Pandemic - Khairunnisya Ilyas; Sukardi Weda; Abdul Halim (ELT Worldwide: Journal of English Language Teaching, 2023)
This comprehensive qualitative study delves into the ramifications of the COVID-19 pandemic on teacher professionalism, particularly in the domain of English language teaching (ELT) in Indonesian senior high schools. Teachers hold a pivotal role in any education system, with their professionalism gauged by the mastery of certain competencies and skills tailored to meet the demands of the teaching profession. In the realm of foreign language education, the overarching goal is to equip learners with essential communication skills, necessitating the design of classroom activities that encourage learners to express themselves effectively through language. The onset of the pandemic posed unprecedented challenges to this goal, forcing a rapid transition to online and offline hybrid learning models and demanding flexibility and innovation from teachers. This study, conducted at MAN 2 Parepare in 2022, explores how English teachers responded to these challenges, analyzing their teaching strategies and techniques to maintain the quality of education amidst this turbulent period. The study identified four primary strategies employed by teachers - expository, inquiry, contextual teaching and learning, and problem-based instruction. Teachers adapted these methods to foster an engaging learning environment that caters to the unique challenges posed by the pandemic, such as virtual classrooms and social distancing measures. The study reveals not only the teachers' adaptability and resilience but also their commitment to nurturing their students' linguistic abilities, even in times of crisis. Furthermore, the study uncovers the difficulties faced by these professionals, providing a clear picture of the pressing need for targeted support and professional development initiatives in these exceptional circumstances. The findings of this research have broad implications for policymakers and educators alike, highlighting the importance of fostering teacher professionalism and adaptability in the face of adversities and contributing to the ongoing discourse on effective English language teaching during a global pandemic.